Suitability of Different Solvents on the Yield of Chlorophyll and Carotenoid Content in Seaweeds - P. Chellamanimegalai; Geetanjali Deshmukhe (Journal of Indian Fisheries Association, 2022)
The pigment extraction was carried out using two different solvents, acetone 80% and dimethyl sulfoxide (DMSO) for red, brown and green seaweeds collected from the Okha coast, Gujarat. The chlorophyll a, chlorophyll b, total chlorophyll and carotenoids extracted from different seaweeds namely Halymenia venusta, Solieria robusta, Halymenia porphyraeformis, Colpomenia sinuosa, Iyengaria stellaa, Caulerpa racemosa, Ulva lobata using 80% acetone ranged from 0.164 to 1.661mg/g; 0.013 to 1.252mg/g; 0.185 to 2.912mg/g and 0.125 to 0.784mg/g, respectively. The chlorophyll a, chlorophyll b and total chlorophyll, and total carotenoids obtained with DMSO solvent for different seaweeds ranged from 0.071 to 1.085mg/g, 0.012 to 1.085mg/g, 0.104 to 2.169mg/g and 0.074 to 2.482mg/g, respectively. Among them, green algae C. racemosa was extracted for a maximum yield of chlorophyll (2.912mg/g) and carotenoids (0.784mg/g) using acetone 80% and the extract obtained from red algae, H. venusta (2.169mg/g) and brown algae C. Sinuosa (1.251mg/g) using DMSO solvent showed the highest amount of total chlorophyll and carotenoids.